Use of Botulinum Toxin in Treating Rosacea: A Systematic Review - Zhang H; Tang K; Wang Y; Fang R; Sun Q (Dove Medical Press, 2021)
Hanlin Zhang,* Keyun Tang,* Yuanzhuo Wang, Rouyu Fang, Qiuning Sun Department of Dermatology, Peking Union Medical College Hospital, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qiuning Sun Tel +86-10-69156114Fax +86-10-69156114Email doctorjenny1@163.comBackground: Rosacea is a chronic skin disorder characterized by erythema, flushing, telangiectasia, papules and pustules, phymatous changes, and ocular involvement. The aim of this study was to examine all published research articles in which botulinum toxin was used to treat rosacea and to evaluate the efficacy and safety of this treatment.Methods: PubMed, Embase, Cochrane Library, and Web of Science database were used to identify articles eligible for systematic review on March 26, 2021. Prospective or retrospective studies which directly used botulinum toxin to treat rosacea were included and reviewed.Results: Nine studies were included in this systematic review. Two were randomized controlled trials, graded as Level 2 for the quality of evidence. The total number of participants was 130, and the number of participants in each study ranged from 1 to 25. The improvement was observed in all studies in signs and symptoms compared with baseline. Adverse events were transitory and self-limited.Conclusion: Botulinum toxin could have overall satisfying efficacy and safety in the treatment of rosacea, though limited by small sample size, imperfect study design, and short follow-up visits.Keywords: botulinum toxin, rosacea, systematic review